2003
DOI: 10.1210/jc.2003-030126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone (GH) Treatment on Bone in Postpubertal GH-Deficient Patients: A 2-Year Randomized, Controlled, Dose-Ranging Study

Abstract: GH treatment in children with GH deficiency is frequently terminated at final height. However, in healthy individuals bone mass continues to accrue until peak bone mass is achieved. Because no prospective data specifically prove the role of GH in attainment of peak bone mass, we performed a multinational, controlled, 2-yr study in patients who had terminated pediatric GH at final height. Patients were randomized to: GH at 25.0 microg/kg x day (pediatric dose, n = 58) or 12.5 microg/kg x day (adult dose, n = 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 19 publications
6
85
0
4
Order By: Relevance
“…These recommendations are based on studies by Drake et al that showed that cessation of GH replacement in adolescents at the completion of linear growth is associated with negligible further gain in median total body bone mineral content (BMC) over 1 year (C2.4%, PZ0.5), whereas adolescents who continue to receive GH replacement continue to increase their median BMC (C6.0%, P!0.001) (56). Shalet et al confirmed these findings with a 2-year, multi-centre, randomised, non-blinded study comparing an adult GH replacement dose (12.5 mg/kg per day) to a paediatric GH replacement dose (25 mg/kg per day) and to no GH replacement in adolescents who had achieved final height; in addition to confirming the adverse effect of non-treatment with GH, this study demonstrated no additional benefit in BMC from the higher GH dose (57). Interestingly, lumbar spine was the area that accrued the most additional BMC with GH therapy, an area particularly at risk from osteoporotic fractures.…”
Section: Bonesupporting
confidence: 53%
See 1 more Smart Citation
“…These recommendations are based on studies by Drake et al that showed that cessation of GH replacement in adolescents at the completion of linear growth is associated with negligible further gain in median total body bone mineral content (BMC) over 1 year (C2.4%, PZ0.5), whereas adolescents who continue to receive GH replacement continue to increase their median BMC (C6.0%, P!0.001) (56). Shalet et al confirmed these findings with a 2-year, multi-centre, randomised, non-blinded study comparing an adult GH replacement dose (12.5 mg/kg per day) to a paediatric GH replacement dose (25 mg/kg per day) and to no GH replacement in adolescents who had achieved final height; in addition to confirming the adverse effect of non-treatment with GH, this study demonstrated no additional benefit in BMC from the higher GH dose (57). Interestingly, lumbar spine was the area that accrued the most additional BMC with GH therapy, an area particularly at risk from osteoporotic fractures.…”
Section: Bonesupporting
confidence: 53%
“…However, mild childhood-onset GHD (peak GH 3-11.8 mg/l on provocation testing) appears to be associated with normal BMD (12) and improvements in BMC have been seen with what could be considered sub-therapeutic IGF1 levels (57). These observations suggest that modest improvements in GH status may be adequate to improve bone outcomes in younger patients.…”
Section: Bonementioning
confidence: 98%
“…The bone abnormalities described in the adults with CO GHD are consistent with the studies of GH deficient post-pubertal patients (mean age 19 years) in whom the acquisition of peak bone mass is sub-optimal if they remain off GH replacement following treatment in childhood (33). It should be emphasised however that the most persuasive evidence that GH replacement significantly increases total BMC in this situation was obtained in severely GH deficient subjects defined by an IGF1 level below the first centile (33).…”
Section: Fracturessupporting
confidence: 83%
“…It should be emphasised however that the most persuasive evidence that GH replacement significantly increases total BMC in this situation was obtained in severely GH deficient subjects defined by an IGF1 level below the first centile (33).…”
Section: Fracturesmentioning
confidence: 99%
“…Bilinmesi gereken önemli bir ayrıntı da tedavinin 12. ayından önce yapılan kemik mineral dansitesinde (KMD) azalma görülebileceğidir [20]. Bu nedenle BH tedavisinin 18-24. ayında KMD ölçülmelidir [21]. BH eksikliği olan çocuklarda erişkin boya ulaşılsa bile iskelet ve kas maturasyonunun maksimum olması için geçiş dönemi boyunca BH tedavisine devam edilmesi önerilmektedir [6].…”
Section: Bh Tedavisinin Faydalarıunclassified